The platelet to lymphocyte ratio in heart failure: a comprehensive review - Delcea Caterina; Buzea Cătălin Adrian; Vîjan Ancuța Elena; Bădilă Elisabeta; Dan Gheorghe-Andrei (Romanian Journal of Internal Medicine, 2023)
Introduction: At the crossroads of heart failure (HF) and systemic inflammation, platelets and lymphocytes are both influenced as well as actively participating in the bidirectional relationship. The platelet to lymphocyte ratio (PLR) could therefore be a marker of severity. This review aimed to assess the role of PLR in HF.